Leptin gene polymorphism of Ongole Grade cattle based on single nucleotide polymorphism - Hilmia, N.; Rahmat, D.; Dudi, D. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
Point mutation on exon 2 of leptin gene, which changes amino acid encoding from Arginine to Cysteine, may alters the physiological function of the leptin hormone. This study aimed to identify leptin gene polymorphism of Ongole Grade (OG) cattle based on Single Nucleotide Polymorphism (SNP). The DNA sample was taken from 48 head of OG cattle at Balai Pengembangan Perbibitan Ternak Sapi Potong(BPPT SP) Cijeungjing West Java, which was isolated from white blood cell using the high salt method. Amplification of DNA was done by Polymerase Chain Reaction (PCR), followed by direct sequencing to obtain nucleotide sequence. The SNP analysis was carried out from alignment of sequencing result using Bioedit and MEGA 5.2 program. The results indicated in exon 2 leptin gene of OG cattle there was one synonymous SNPs that did not changeamino acids Serine encoding on g.1025T >C/S17S, while two non synonymous SNPaltered amino acids encoding, those were g.1047C> T /R25C and g.1048G>A/R25H. Those mutations changed amino acids encoding from Arginine to Cysteine and Arginine to Histidine respectively.In OG cattle, the frequency of A allele (44.8%) was higher than C allele (33.3%) and T allele (21.9%). Six genotypes were also identified, i.e. AA (41.7%), CC (20.8%), CT (20.8%), CA(4.2%), TT (10.4%) and TA (2.1 %). Heterozigosity of OG cattle based on leptin gene was 0.65 that was a high category. The A allele was a specific allele on Indonesian local cattle.